O feminino como monstruoso no cinema - Barbosa, Ana Caroline Fogaça (2023)
The present work has as object of study the female body in the cinematographic representations of the last decade that constitute the corpus of the work. They are: Black Swan (dir. Daren Aronofsky, 2010, USA), Under The Skin (dir. Jonathan Glazer, 2014, Switzerland, UK, USA), In Fabric (dir. Peter Strikland, 2018, UK) and The Skin I Live In (La Piel que Habito, dir. Pedro Almodóvar, 2010, Spain). The study proposes to analyze these works and identify present aesthetic elements that act as manifestations of the monstrous feminine and have been reappearing throughout the history of the West. For this, the historical construction of the concept of monster is presented, establishing its connection with the feminine, relating it to psychoanalytic conceptions and mainly to historical events. Afterwards, the analytical instrument used is developed, introducing the concepts that gave rise to the historical investigation of the images used by Adriano Denovac, namely the reminiscent lapses and the concepts that originated it. These are related to the theories of Aby Warburg and Didi-Huberman as they deal with the reappearance of images in time. Such reappearances are discussed due to the strength of these images, which lead them to survive in time considering social and collective contexts. With this, an aesthetic discussion is brought about the image as a sinister experience through image stimuli explained by psychoanalytic theory. This supports the demonstration of how cinema acts as a cultural manifestation, as means of communication with its own language codes, to then develop the analyses. These demonstrate the way in which the images are constructed over time, their relationships with the psychic, social, cultural constitution and critical observations on the different perspectives offered on the image of the female body.